Upaya Meningkatkan Minat Siswa – Siswi Terhadap Olahraga Kasti Dengan Model Pembelajaran Direct Intruction Di SMPN 1 Kalimanggis - Yosep Alpualik Sidik; Didi Muhtarom (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to increase students' interest in the sport of rounders with the Direct Instruction learning model. This research will be carried out at SMPN 1 Kalimanggis with research subjects being class VIII students at SMPN 1 Kalimanggis for the 2023/2024 academic year, and the sample used is class VIII A. This research is quantitative research with the type of pre-experimental research (pre-experimental designs) used in this research being one-group pre test – post test design. The research instruments used were observation and questionnaires using a Likert scale. The questionnaire or questionnaire will later be distributed twice during the pre-test and post-test. Before the post-test, the researcher will carry out treatment to deepen the material on baseball for the students. After the pre-test - post-test is carried out, the researcher will carry out data processing to determine the students' interest in the sport of rounders.